مدخل مقترح لتدقيق الجودة (ISO) كأحد أنواع الفحص لأغراض خاصة - العدناني محمد هادي (Journal of Economics and Administrative Sciences, 2007)
This research seeked to create frame work for audit ISO as one class of investigation for special purpose. The suggestion frame work depend on five basic ingredients, there were nature of ISO audit, the people interested requirements to do this audit who process the audit and the problems effect this audit. Already discussed and study the requirements and recommendations from International Standardization Organization. The researcher suggested the basic supposition which (the ISO audit considered as one class of investigations special purpose which required from many parties and performances by various auditors) This study depend on scientific study depended on analytical approach for ISO cases study (ISO literatures). Also audit and investigations cases study which the researcher find for study and discussed for purpose for tested the basic supposition and inquired the research aim. After the study and the discussion the researcher reached many restates mentioned in this study. There were the important recommendations as follows: 1- More field researches for valuation ISO audit in Iraqi environment. 2- Include ISO audit in auditing and control topic in under graduate and post control in universities. 3- Prepare training sessions for internal and external auditors to be more profession adaptation with ISO audit.